Research progress on the microecological strategies of root caries management - WU Lijing; TAO Yiwei; ZENG Bo; CAI Yanling (口腔疾病防治)
Root caries is a prevalent chronic oral disease with an average global prevalence of 41.5%, characterized by high incidence, low rate of treatment, and high rate of retreatment. Root caries is primarily caused by core microbiome-induced dysbiosis and has multiple risk factors, including gingival recession, root surface exposure, and salivary dysfunction. The traditional preventive measures and treatments such as fluoride, mineralizing agents, and restorative materials, are unable to restore or maintain oral microecological homeostasis. Recent studies have demonstrated that probiotics, prebiotics, synbiotics, and antimicrobial peptides may prevent and treat root caries by reversing dysbiosis. In addition, these biotherapeutics can reduce acid production by acidiferous bacteria, promote alkali production (hydrogen peroxide and ammonia) by alkali-producing bacteria, inhibit biofilm formation, decrease extracellular polysaccharide production, and suppress microbial adhesion and aggregation. It is expected to play an important role in the prevention and control of root caries. This article aims to review oral probiotics (Streptococcus oligofermentans, Streptococcus oralis subsp. dentisani, and Streptococcus salivarius), prebiotics (arginine, nitrates, and synthetic compounds), synbiotics, and antimicrobial peptides (gallic acid-polyphemusin I and LH12) to provide evidence and guidance for root caries management through microecological modulation.